Teacher Perceptions of the Use of Learning Multimedia in the Merdeka Curriculum for Strengthening the Character of Students - Rahma Yanthi (Science Center Group, 2024)
Background: The Merdeka Curriculum in Indonesia emphasizes project-based learning and character education as essential components of twenty-first-century competencies. The integration of learning multimedia has been recognized as a strategic tool to enhance instructional quality and foster students’ character development; however, teachers’ perceptions play a crucial role in determining its effective implementation. Objective: This study aimed to analyze teachers’ perceptions of the use of learning multimedia in the Merdeka Curriculum and its impact on strengthening students’ character. Methods: A qualitative descriptive case study design was employed. Participants consisted of 10–15 teachers selected through purposive sampling from schools implementing the Merdeka Curriculum and actively utilizing multimedia in classroom instruction. Data were collected through in-depth semi-structured interviews and classroom observations. Thematic analysis was conducted through data reduction, data display, and conclusion drawing. Triangulation of interview and observational data was applied to enhance validity and credibility. Results: The findings revealed that most teachers held positive perceptions of multimedia use in the Merdeka Curriculum. Teachers reported that multimedia enhanced student engagement, facilitated the understanding of abstract concepts, and supported the internalization of character values such as responsibility, cooperation, tolerance, and curiosity. However, challenges related to limited technological infrastructure and insufficient technical support were identified as barriers to optimal implementation. Teachers who had received professional training demonstrated higher confidence and competence in integrating multimedia for character education. Conclusion: Teachers generally perceive learning multimedia as an effective instrument for strengthening students’ character within the Merdeka Curriculum framework. Positive teacher perceptions, adequate infrastructure, and continuous professional development are critical factors in optimizing multimedia integration for holistic character education